Birding while Indian : a mixed-blood memoir - Gannon, Thomas C. (Machete., 2023)
"Catalogs a lifetime of bird sightings to explore the part-Lakota author's search for identity and his reckoning with colonialism's violence against Indigenous humans, animals, and land."--